Reposisi Penciptaan Tari Minangkabau Baru: Media Hiburan dan Pelestarian Kearifan Lokal - Mia Fahmiati; Hana Shilfia Iraqi (FBS Universitas Negeri Padang, 2023)
This article aims to analyze the position of Minangkabau dance creations as entertainment and as a preservation of Minangkabau local wisdom. In addition, this article introduces creative dance as a new culture for the people of West Sumatra which has an impact on preserving Minangkabau local wisdom. This study uses a qualitative method where data is collected through interviews, observation, and a literature review of Minangkabau contemporary dance creations. The validity of the data was tested through triangulation and analyzed based on the phenomena contained in the Minangkabau creative dance and then verified. The results of the study found that the existence of Minangkabau creative dance today is a form of representation of Minangkabau local wisdom so that creative dance can be accepted by the Minangkabau people in West Sumatra. Minangkabau dance creations are in the process of creation and cannot be separated from the acculturation and reconstruction of Minangkabau dance traditions that once existed. In turn, this creative dance can maintain the existence of Minangkabau traditional dance as a cultural heritage of the Minangkabau people. Dance created by Minangkabau during this period has a position as public entertainment and as a medium for preserving the local wisdom values of the Minangkabau people.